Intake assessment of L-ergothioneine in some European countries and in the United States. Issue 3 (2nd April 2016) - Ramirez-Martinez, Alejandra; Wesolek, Nathalie; Yadan, Jean-Claude; Moutet, Marc; Roudot, Alain-Claude
ABSTRACT: L-ergothioneine is an amino acid synthetized by fungi and mycobacteria that cannot be synthesized by other species. It has been detected in plants, animals, and the human body. In the last few years, it has been recognized as a good antioxidant and, recently, it has also been related to other properties besides antioxidant properties. Even though few studies on the toxicity of L-ergothioneine have been carried out, evidence suggests that L-ergothioneine is not harmful to health. Considering that L-ergothioneine has increasingly been linked to positive effects on human health, coupled with the fact that it seems to be safe for human consumption, this molecule may be suitable for use as an ingredient in foods. On the other hand, despite the positive effects reported for this molecule, no estimate of L-ergothioneine intake has been carried out until now. Thus, the aim of this work is to estimate the intake of L-ergothioneine through food consumption of several European countries and the United States. Values were estimated by using the deterministic and probabilistic approach. Results show that the populations with the highest intake of L-ergothioneine correspond to Italian population, both for children and adults.